2020
DOI: 10.1186/s12933-019-0978-y
|View full text |Cite
|
Sign up to set email alerts
|

Fasting plasma glucose variability and HbA1c are associated with peripheral artery disease risk in type 2 diabetes

Abstract: Background: This study investigated whether visit-to-visit fasting plasma glucose (FPG) variability, as measured by the coefficient of variation (CV), increased peripheral artery disease (PAD) risk.Methods: Individuals with type 2 diabetes from the National Diabetes Care Management Program during the period 2002-2004, ≥ 30 years of age, and free of PAD (n = 30,932) were included and monitored until 2011. Cox proportional hazards regression models were implemented to analyze related determinants of PAD.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
3
18
0
2
Order By: Relevance
“…In addition, the prevalence of PAD was significantly higher in patients on oral hypoglycemic drugs than in insulin users due to the majority of participants used 2 or 3 oral hypoglycemic drugs or mixed therapy and were not compliant. This study agrees with Yang et al (16) who showed that PAD was significantly higher in patients on oral hypoglycemic drugs than in insulin users. In contrary, Yeboah et al (17) showed that PAD was more frequent in insulin users due to the effect of insulin resistance on atherosclerosis progression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the prevalence of PAD was significantly higher in patients on oral hypoglycemic drugs than in insulin users due to the majority of participants used 2 or 3 oral hypoglycemic drugs or mixed therapy and were not compliant. This study agrees with Yang et al (16) who showed that PAD was significantly higher in patients on oral hypoglycemic drugs than in insulin users. In contrary, Yeboah et al (17) showed that PAD was more frequent in insulin users due to the effect of insulin resistance on atherosclerosis progression.…”
Section: Discussionsupporting
confidence: 93%
“…The means of FBS, 2 hrPPBS and HBA1c were significantly higher in PAD group than in non-PAD group. This study agrees with Shaikh et al (9) and Yang et al (16) regarding that FBS and HBA1c levels were higher in patients with PAD. In contrast, Cornejo Del Río et al (21) showed no significant difference between studied groups regarding FBS and 2 hrPPBS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study enrolled 420 T2DM patients and suggested that visit-to-visit HbA1c variability expressed as SD, CV and VIM was independently associated with incidence of in-stent restenosis in patients with T2DM after stent implantation [ 61 ]. Of note, several studies disclosed that long-term GV including both HbA1c and FPG variability (calculated by CV) was associated with peripheral artery disease risk and accelerated progression of coronary atherosclerosis in patients with T2DM [ 62 , 63 ]. These clinical results addressed the essential role of GV in diabetic macrovascular complications (Table 2 ), and paved the way for the research on relevant mechanisms.…”
Section: The Role Of Gv In Diabetic Macrovascular and Microvascular Cmentioning
confidence: 99%
“…Bertrand et al demonstrate that HDL-cholesterol, ApoA-I, total cholesterol/HDL-cholesterol ratio or non-HDL-cholesterol were independent factors associated with PAD in patients with type 2 diabetes [13]. Fasting plasma glucose, hemoglobin A(1c), homocysteine levels, age, duration of diabetes, hypertension, cigarette smoking, serum creatinine, estimated glomerular filtration rate, and urinary albumincreatinine ratio history of myocardial infarction and stroke have been also reported to be associated with PAD [14][15][16][17].…”
mentioning
confidence: 94%